2012
DOI: 10.1111/j.1939-1676.2012.00911.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Application of Lidocaine and Sodium Bicarbonate in the Treatment of Obstructive Idiopathic Lower Urinary Tract Disease in Cats

Abstract: BACKGROUND: In human patients with interstitial cystitis, intravesical instillation of alkalinized lidocaine sometimes is associated with sustained amelioration of symptoms beyond the acute treatment phase. Interstitial cystitis shares many features in common with feline idiopathic cystitis. OBJECTIVE: To evaluate whether intravesical instillation of alkalinized lidocaine decreases recurrence of urethral obstruction and severity of clinical signs in cats with obstructive idiopathic LUTD. ANI-MALS: Twenty-six c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
0
10
4
Order By: Relevance
“…In the present study, the rates of rUO in the PPS and placebo group (16.7% and 17.6%, respectively) were lower than previously reported with recurrence rates of 58% within 3 days and 36% within 17 days, 18,20 whereas other studies observed a recurrence rate of 15% (observation period of 2 months) in cats with UO of any cause and 22% (observation period of 6 months) in cats with obstructive FIC. 19,45 Variable inclusion criteria (FIC and UO of any cause), study designs (prospective and retrospective), as well as a different medical management (eg, use of α-sympatholytic drugs or no α-sympatholytic drugs) and follow-up periods could have influenced the different rates of rUO.…”
Section: Discussioncontrasting
confidence: 90%
“…In the present study, the rates of rUO in the PPS and placebo group (16.7% and 17.6%, respectively) were lower than previously reported with recurrence rates of 58% within 3 days and 36% within 17 days, 18,20 whereas other studies observed a recurrence rate of 15% (observation period of 2 months) in cats with UO of any cause and 22% (observation period of 6 months) in cats with obstructive FIC. 19,45 Variable inclusion criteria (FIC and UO of any cause), study designs (prospective and retrospective), as well as a different medical management (eg, use of α-sympatholytic drugs or no α-sympatholytic drugs) and follow-up periods could have influenced the different rates of rUO.…”
Section: Discussioncontrasting
confidence: 90%
“…4 Repeat urethral obstruction rates in male cats vary by the report and the cause of obstruction, but were 36% and 58% in two recent studies. 4,5…”
Section: Short Communicationmentioning
confidence: 99%
“…4 Repeat urethral obstruction rates in male cats vary by the report and the cause of obstruction, but were 36% and 58% in two recent studies. 4,5 A defective glycosaminoglycan (GAG) layer lining the urinary bladder mucosa has been proposed as both a cause and effect of FIC, as well as being involved in interstitial cystitis in humans. 2,[6][7][8] Urothelial permeability increases with defects in surface GAGs, which could lead to increased contact of urine with bladder wall tissues, resulting in the induction of immune-mediated or neurogenic inflammation, mast cell activation and sensory afferent nerve stimulation.…”
mentioning
confidence: 99%
“…1 The survival to hospital discharge for cats with UO is excellent [1][2][3] ; however, recurrence rates ranging from 22 to 57% are reported in the veterinary literature. 2,4 In one report, the median time from initial relief of UO to recurrent urethral obstruction (rUO) was 17 days, with 80% of the cats developing recurrent lower urinary tract signs (eg, stranguria, hematuria, pollakiuria) within 16 days of hospital discharge. 3 Unfortunately, recurrence of lower urinary tract signs or rUO may result in death or euthanasia of the cat.…”
Section: Introductionmentioning
confidence: 99%
“…Feline urethral obstruction (UO) is a common emergency, and accounted for 10% of feline emergency admissions at one veterinary teaching hospital . The survival to hospital discharge for cats with UO is excellent; however, recurrence rates ranging from 22 to 57% are reported in the veterinary literature . In one report, the median time from initial relief of UO to recurrent urethral obstruction (rUO) was 17 days, with 80% of the cats developing recurrent lower urinary tract signs (eg, stranguria, hematuria, pollakiuria) within 16 days of hospital discharge .…”
Section: Introductionmentioning
confidence: 99%